2019
DOI: 10.1186/s40985-019-0115-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of health outcome and health service utilization indicators as an outcome of access to medicines in Brazil: perspectives from a literature review

Abstract: BackgroundTo guarantee the right to health, the health system must also ensure access to medicines. Several financial arrangements to provide these technologies are implemented and range from the direct (either total or partial) to indirect payment by the patient, being necessary to evaluate its effect on access to medicines. However, to ensure access to medicines is not just about ensuring its availability, as this only materializes in its use. Thus, evaluation studies of interventions in access to medicines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Healthcare use can be defined as the quantification or description of the use of services by persons for the purpose of preventing and curing health problems, promoting maintenance of health and well-being, or obtaining information about one’s health status and prognosis [ 41 ]. Indicators of healthcare use include GP consultations, hospital visits including inpatient, outpatient and day visits, hospital admissions, accidents and emergency department visits, diagnoses, prescriptions, referrals, immunisations and screening [ 29 , 42 , 43 ]. In contrast, healthcare quality has been defined as the degree to which healthcare services increase the chances of desired health outcomes for people and are aligned with current professional knowledge [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Healthcare use can be defined as the quantification or description of the use of services by persons for the purpose of preventing and curing health problems, promoting maintenance of health and well-being, or obtaining information about one’s health status and prognosis [ 41 ]. Indicators of healthcare use include GP consultations, hospital visits including inpatient, outpatient and day visits, hospital admissions, accidents and emergency department visits, diagnoses, prescriptions, referrals, immunisations and screening [ 29 , 42 , 43 ]. In contrast, healthcare quality has been defined as the degree to which healthcare services increase the chances of desired health outcomes for people and are aligned with current professional knowledge [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…The search was limited to the year 2010 onwards to allow for the identification of recent evidence. As the aim of this study was to support health systems planning, only healthcare service utilisation reported from a health systems perspective was included, such as a) Hospital utilisation, b) Emergency department (ED) utilisation, c) Medication utilisation, and d) Primary care utilisation [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…As a result of the lack of responsiveness and age of the generic measures, they are being replaced by disease-specific PROMs. However, in medium and low-income countries, there is a lack of comprehensive information systems, creating methodological obstacles in evaluation studies and limiting the capacity to conduct longitudinal studies 3 . Healthcare professionals, researchers and pharmaceutical companies are therefore reliant on generic outcome measures to collect information from patients because, theoretically, they can be used with any patient population.…”
Section: Introductionmentioning
confidence: 99%